Il viaggio come esperienza di formazione. Tra diacronia e sincronia - Franco Cambi (Firenze University Press, 2012)
The trip is part of vital experience of the man. Yesterday and today. But travelling has changed during the historical process. It has advanced and it's complicated, according to different models (pilgrimage, Grand Tour, touristic trip) and showing the complexity of his social and cultural role: also and above all educational.